2021
DOI: 10.18415/ijmmu.v8i3.2494
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Inflation Rate, Exchange Rate, The Certificate of Bank Indonesia (SBI) Interest Rate and Sharia Stock Trading Volume on Sharia Stock Performance in Companies Listed on the Indonesian Sharia Stock Index (ISSI)

Abstract: This study aims to determine and analyze the effect of the inflation rate, exchange rate, SBI interest rate and Sharia stock trading volume on the performance of Sharia stocks in companies listed on the Indonesian Sharia Stock Index. In this study, a research model was created using Sharia stock performance as the dependent variable. While the independent variables are the inflation rate, exchange rate, certificate of Bank Indonesia (SBI) interest rate and Sharia stock trading volume. The research method used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 0 publications
1
8
1
1
Order By: Relevance
“…According to the IRF analysis, an increase in SBIS has a positive effect on economic performance. This research contradicts to the findings of Asnuri (2013), Bassar et al (2021) and Wibowo and Mubarok (2017). In a nutshell, it can be said that the increase in SBIS used by the monetary authority is effective in increasing the economic performance.…”
Section: ~352~contrasting
confidence: 74%
See 2 more Smart Citations
“…According to the IRF analysis, an increase in SBIS has a positive effect on economic performance. This research contradicts to the findings of Asnuri (2013), Bassar et al (2021) and Wibowo and Mubarok (2017). In a nutshell, it can be said that the increase in SBIS used by the monetary authority is effective in increasing the economic performance.…”
Section: ~352~contrasting
confidence: 74%
“…Studies conducted by Ascarya (2012), Bassar et al (2021), and Madani and Widiastuti (2021) show that SBIS has a positive impact on the economic performance, while research by Wibowo and Mubarok (2017) shows the opposite result. In terms of IIMM instrument, a study conducted by Setiawan and Karsinah (2016) showed a positive relationship on the performance of economic, while the research of Zaelina (2018) showed a negative correlation.…”
Section: ~339~mentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies also show that only the GDP has a significant effect on the stock price index of the plantation sector, and variables such as interest rates, inflation rates, and the Rupiah exchange rate against the Dollar do not have a significant effect on the stock price index of the plantation sector (Safitri & Kumar, 2014). Recent literature on the impact of macroeconomics on the stock market in Indonesia can also be tracked through research by Augustpaosa Nariman (2019), Bassar et al (2021), Lusiana (2020), and Maharditya et al (2018 However, specific studies on the relationship between macroeconomic variables and banking stocks in Indonesia are limited. One of the studies in the Indonesian banking issuers through the monthly price index for the period 2010-2015 show that inflation and exchange rates positively affect the stock price index while interest rates negatively affect it.…”
Section: Public Interest Statementmentioning
confidence: 99%
“…Umaryadi et al (2021) documented a positive but insignificant relationship between inflation and stock returns. Bassar et al (2021) failed to find any significant effects of inflation on Shariah stock returns, thus suggesting that Shariah stocks can be considered a viable hedging instrument in times of high inflation. Asiedu et al (2021) indicate that inflation has a negative effect on the overall stock market performance in the long run.…”
Section: Introductionmentioning
confidence: 99%